1999
DOI: 10.1155/mbd.1999.41
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐Candida Activity of Cobalt(II) Complexes ofBenzene‐1,2‐Dioxyacetic Acid (bdoaH2). X‐Ray Crystal Structures of [Co(bdoa)(H2O)3]⋅3.5H2O and {[CO(phen)3](bdoa)} 2⋅24H2O (phen = 1,10‐Phenanthroline)

Abstract: Co(CH3CO2)2⋅4H2O reacts with benzene-1,2-dioxyacetic acid (bdoaH2) to give the Co2+ complexes [Co(bdoa)(H2O)3]⋅H2O (1a) and [Co(bdoa)(H2O)3] ⋅3.5H2O (1b). Subsequent reaction of 1a with 1,10- phenanthroline produces [CO(phen)3] bdoa⋅10H2O (2a) and {[CO(phen)3](bdoa)}2⋅24H2O (2b). Molecular structures of 1b and 2b were determined crystallographically. In 1b the bdoa2-- ligates the metal by two carboxylate oxygens and two ethereal oxygens, whereas in 2b the bdoa2- is uncoordinated. The Mn2+ and Cu2+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…MIC of 1,10-phen, metal-l,10-phen complexes and selected starting materials on C. It is significant that Ag(CH3CO2) is the only complex not to contain 1,10-phenanthroline but to exhibit activity similar to that of metal-free 1,10-phen and other metal complexes containing the 1,10-phen ligand. Previous studies have shown that the MIC values of simple metal acetates (metal Mn(II), Cu(II) and Co(II)) 44 is >20 gg cm-3. In addition, by studying the anti-Candida activity of a series of complexes (concentration 20 gg cm"3) of general formula [M(1,10-phen)n]Xy (M Mn(II), Cu(II), Zn(II); X malonate, acetate, chloride) it was established that the nature of the counter anion X does not influence the inhibitory effect (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…MIC of 1,10-phen, metal-l,10-phen complexes and selected starting materials on C. It is significant that Ag(CH3CO2) is the only complex not to contain 1,10-phenanthroline but to exhibit activity similar to that of metal-free 1,10-phen and other metal complexes containing the 1,10-phen ligand. Previous studies have shown that the MIC values of simple metal acetates (metal Mn(II), Cu(II) and Co(II)) 44 is >20 gg cm-3. In addition, by studying the anti-Candida activity of a series of complexes (concentration 20 gg cm"3) of general formula [M(1,10-phen)n]Xy (M Mn(II), Cu(II), Zn(II); X malonate, acetate, chloride) it was established that the nature of the counter anion X does not influence the inhibitory effect (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our earliest studies had shown that hydroxynitro coumarin derivayives were selectively active against cancer-derived cell lines but later studies had shown that complexation of hydroxynitrocoumarin ligands, and indeed complexation of many other ligands, to metal centres increases the bioactivity of these compounds significantly [22][23][24][25][26][27][28][29][30]. The discovery of the antitumour drug cisplatin and its derivatives has aroused huge interest in metal-based chemotherapeutics and has led to the discovery of new alternative non-platinum based anticancer agents [31,32].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Such interaction with transition metal ions with amino acids, peptides and nucleic acids, are of immense biological importance [14][15][16]. Several reviews [17][18][19][20] showed that the metallo-organic chemistry of such compounds greatly influence their biological action highlighting the catalytic function metals [21][22][23] in many biological processes. H. Chohan et al [24] was reported some substituted pyridine Schiff bases obtained from salicylaldehyde and showed good antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%